Cribrilinidae (Bryozoa: Cheilostomata) of Korea - Yang, Ho Jin; Seo, Ji Eun; Min, Bum Sik; Grischenko, Andrei V.; Gordon, Dennis P. (Zootaxa, 2018)
The cribrilinid Bryozoa of Korea are described for the first time. Eight species are recognized, distributed in five genera: Cribrilina, Reginella, Jullienula, Figularia and Puellina. Juxtacribrilina n. subgen. is recognized as comprising a group of species within Cribrilina characterized, inter alia, by having adventitious avicularia, reduced and/or vestigial ooecia, a pair of proportionately long protective latero-oral costae that cross the front of the ooecium and fuse in the midline, and a cribrimorph ancestrula. Cribrilina (Juxtacribrilina) flavomaris n. sp., Jullienula erinae n. sp. and Puellina paracaesia n. sp. are so far known only from the west and southwest coasts of the Korean Peninsula. The following six new combinations are recognized: Cribrilina (Juxtacribrilina) annulata (Fabricius, 1780) n. comb., Cribrilina (Juxtacribrilina) corbicula O’Donoghue & O’Donoghue, 1923 n. comb., Cribrilina (Juxtacribrilina) mutabilis Ito, Onishi & Dick, 2015 n. comb., Reginella multipora (Sakakura, 1935) n. comb., Reginella biporosa (Okada, 1923) n. comb. and Jullienula ortmanni (Silén, 1941) n. comb.